Pendekatan, Strategi, Metode dan teknik Dalam Pembelajaran PAI Di Sekolah Dasar - Fadhlina Harisnur; Suriana (PGMI IAIN Lhokseumawe, 2022)
The learning process engineering can be designed by educators in such a way. Ideally, the learning approach for smart students should be different from the activities of students with moderate or low abilities (although to understand the same concept). This is because, each student has a uniqueness that is different. This indicates that educators' understanding of approaches, models, strategies, methods, and learning techniques cannot be ignored. This is because teaching and learning activities are closely related to the process of seeking knowledge. For this reason, education must be in accordance with the demands of the times, always improving and developing plans and methods in the learning process. Approaches, strategies, methods and learning techniques are components of learning that must be mastered by educators so that learning objectives can be achieve